Irregularity of MBS Second Semester Students of Tribhuvan University: Causes and Effects on their Academic Performance - Daman Bahadur Singh (Interdisciplinary Journal of Management and Social Sciences, 2022)
Regularity is one of the important characteristics of the students. It measures the overall discipline of the students. In Nepal, different universities are run by the government as well as private sectors. Regular attendance is not maintained by the students because of different factors. The objectives is to investigate causes of irregularity and analyze its effects on the student’s overall academic performance are two main objectives of this study. Quantitative research design and Semi-structured questionnaire was considered in this research. A probability sampling design (Stratified Random Sampling) was used to select 150 units from the T.U constituent campuses and T.U. affiliated private (3/10) campuses located in the Kathmandu Valley. The finding of the study is different factors like employment, marital status, age, nature of subjects, and effective lecture are the key factors to make students irregular in college. Regularity and academic performance were highly correlated. Students who were regularly on campus had very good academic performance otherwise bad academic performance. Pearson’s coefficient of correlation was +0.873, Regression coefficient byx=0.873 Value of R2=0.761. The conclusion of the study is irregularity rate in the MBS level of T.U. is very high, and academic performance and regularity in the class are highly correlated, if regularity is maintained then it caused very good academic performance. Different factors caused the irregularity of the students on campus. Strict rules and regulations should be formulated to make students regular. The syllabus should be updated from time to time and strict rules and regulations should be applied to make this program effective.